Deprivation of Land Tenure to Daughters of Mother Earth - Sonene Nyawo (African Journal of Gender and Religion (AJGR))
The judicial system in Eswatini operates on the basis of Roman-Dutch common law and Swazi customary law and administers land occupancy through the dual landholding system of freehold title and Swazi nation land. Tenure over Swazi nation land is governed by Swazi customary law and not defined by legislation. Instead, land is controlled and held in trust by the King and is allocated by chiefs according to traditional non-codified provisions. Whilst Section 211 of the Swazi Constitution (2005) provides that “a citizen of Swaziland, without regard to gender, shall have equal access to land for normal domestic purposes”, traditional leaders, who routinely run the administration of the Swazi nation land and customary land tenure, often ignore it. Ordinarily, only male household heads are eligible to secure land through the customary process known as “kukhonta” that initiates males into the chiefdom and marks their commitment and allegiance to the chief. Under Swazi law and custom, a women can only be granted land rights by the chief through her husband, male relatives, or male children. This paper argues that women are alienated from the land rights that Mother Earth has bequeathed to all humanity despite the similarities of women’s lived experiences and that of the environment. Three (3) scenarios found through library research are cited as examples of Swati women’s lived experiences with regard to land accessibility. The paper concludes by noting that the implementation of Agenda 2030 for sustainable development, and particularly Sustainable Development Goal number 5 (SDG 5), which is geared towards establishing gender equality and empowering all women and girls, can amongst other initiatives be achieved through equal land rights granted to all the children of Mother Earth. However, unless and until societal constructs on land acquisition and ownership are reinterpreted, Emaswati women will continue to receive only the breadcrumbs that fall from the master’s table.